Modern cataloguing (Anmol Pubications, 2001)
Contents of meterial: 1/ Introduction. 2/ Functions of a Library catalog. 3/ Online cataloguing systems. 4/ Cataloguing networks. 5/ Construction of catalog. 6/ Multimedia cataloguing. 7/ Copy cataloguing. 8/ Managing the catalog department. 9/ Cataloguing technologies. 10/ Analytical cataloguing. 11/ Rules for the compilation of catalog.